THE ESSENCE, SEQUENCE AND OTHER PATTERNS OF PROCEDURAL, CRIMINALISTICAL AND EXPERT WORK WITH EVIDENCE AND THEIR SOURCES IN CRIMINAL PROCEEDINGS - Lykhova, Sofiia; Lantsedova, Yuliia; Herontieva, Alona (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the development of innovative understanding of the essence, sequence and other patterns of procedural, criminalistical and expert work with evidence and their sources in criminal proceedings, consisting of seven main stages. Methods: comparative legal analysis, cognitive-analytical, etc. Results: it is proposed to use these innovations as a doctrinal, projected legislative and other applied basis for initiating a broad correct scientific discussion in order to develop a generally accepted solution to this problem. Discussion: based on the analysis of the main points of view, the proposed in the literature version of the innovative understanding of the essence, sequence and other patterns of procedural, criminalistical and expert work with evidence and their objective, subjective and mixed sources in criminal proceedings is supported and developed. Attention is drawn to the presence in this procedure of such basic stages of work, as clarifying the nature, sequence and other patterns of work with such sources of evidence, interconnected versioning, planning and organization of this work, involvement of personal sources and collecting tracesubstances and subjective, objective and mixed documents, obtaining from these sources the evidence and their general evaluating, including verification, and using in criminal proceedings, as well as documentation of the procedure and circumstances of establishment of the subjective sources (tracksubstances, objective documents) and subjective sources (personal sources, subjective or mixed documents), obtaining evidence from them, their evaluation and use in evidence.